Big Data Mergers in the European Union: Regulatory Responses to Data-Related Concerns - Valiyeva,Aynur (2024)
The EU Merger Review regulates mergers with a Community dimension in the EU, assessing if they can be considered a concentration and if this concentration can hinder effective competition. The Commission assesses whether notified mergers are compatible with the common market and has established its own practice in line with EU merger legislation. Big Data companies, such as GAFAM, have gained significant market power by expanding into large digital ecosystems and adding more value to their datasets. The Commission is considering effect-based analyses and theories of harm to address these concerns. Traditional and non-traditional theories of harm are discussed in the thesis. As a response to merger concerns in digital markets, the Commission has revised its Market Definition Notice to address data-related competition concerns, including the “small but significant non-transitory decrease of quality” (SSNDQ) test and principles for defining markets like multi-sided platforms, after-markets, bundles, and digital ecosystems. However, it is under question if such a broad approach can balance innovation and competition in digital markets.
Keywords: Big Data; Mergers and Acquisitions; Competition law